Prevalence of Post-Operative Anaemia and its Complications among Obstetric and Gynaecological Patients in Enugu - IJ, Onyekpa; BU, Odugu; SO, Nweze (Jour Med Resh and Health Sci, 2022)
Background: Anaemia is a common condition among patients especially in the developing world. The prevalence of post-operative anaemia varies widely from centre to centre across all surgical specialties. It is often a reflection of pre-operative anaemia and poor pre-operative work-up. Some modifiable risk factors associated with anaemia include ignorance, illiteracy and poverty, and these factors are more in the developing countries of the world. Post-operative anaemia is associated with various complications which may include wound sepsis, poor wound healing, pneumonia, venous thrombosis, stroke, delirium, acute myocardiac infarction and cardiac failure. The consequences of these complications could range from increased cost of treatment to increased length of hospital stay and to mortality. Aim: To determine the prevalence and complications of post-operative anaemia among obstetric and gynaecological patients in a tertiary hospital Materials & method: It was a prospective, cohort study of 320 women who had surgery in the department of obstetrics and gynaecology for either obstetric or gynaecological indications. Data was collected using a structured proforma and analyzed using Statistical Package for Social Sciences(SPSS) version 20.0 for Windows and the results presented in tables, charts, means, frequencies and percentages Results: The results showed that 320 participants were recruited into the study and they all completed the surgery. Majority of them were aged 36 years and above (37%), married (67.2%) and self-employed (53.1%). The prevalence of post-operative anaemia was 53.8%. The mean post-operative PCV was 28.84± 3.67 and p-value of 8.06(.001). Out of the 320 participants, 194(60.06%) had elective surgeries and 59(46.5%) of them had post-operative anaemia. On the other hand 126(39.4%) had emergency surgeries of which 68(53.5%) had post-operative anaemia (p-value of 0.001). Furthermore, 40(12.5%) of the 320 participants had surgical wound infections; 32(80%) of them had anaemia while 8(20%) had normal, acceptable pcv levels.